Nanomechanical and Charge Transport Properties of Two‐Dimensional Atomic Sheets. Issue 3 (25th February 2014) - Park, Jeong Y.; Kwon, Sangku; Kim, Jong Hun
<x xml:space="preserve">Abstract</x> The materials properties of graphene and other two‐dimensional atomic sheets are influenced by atomic‐scale defects, mechanical deformation, and microstructures. Thus, for graphene‐based applications, it is essential to uncover the roles of atomic‐scale defects and domain structures of two‐dimensional layers in charge transport properties. This review highlights recent studies of nanomechanical and charge transport properties of two‐dimensional atomic sheets, including graphene, MoS2, and boron nitrides. Because of intrinsic structural differences, two‐dimensional atomic sheets give rise to unique nanomechanical properties, including a dependence on layer thickness and chemical modification that is in contrast to three‐dimensional continuum media. Mapping of local conductance and nanomechanical properties on a graphene layer can be used to image the domain and microstructures of two‐dimensional atomic layers. This paper also reviews recent experimental and theoretical findings on the role of bending, defects, and microstructures on nanomechanical and transport properties of graphene‐derived materials.